2010
DOI: 10.1080/15257770.2010.518185
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic Esters of Acyclovir-Synthesis and Biological Activity

Abstract: In the present study we have synthesized esters of acyclovir with cinnamic acids (p-coumaric, ferulic, and sinapic acids) and evaluated them for their antiviral and antioxidant potential. The antiviral activity of the newly synthesized compounds has been tested against human herpes virus 1 (HSV-1) in vitro. The results indicate that none of the synthesized compounds inhibits the tested virus strain. The antioxidant properties have been studied using 2,2-diphenyl-1-picrylhydrazyl (DPPH)* test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, the syntheses of long chain esters of acyclovir (laurate and palmitate) have been referenced only in the Gao et al 17) review in which yields of 37% are reported. Recently, Stankova et al 18,19) described the synthesis of acyclovir esters with peptidomimetics or with cinnamic acid using coupling reagents and evaluated in vitro for their antiviral activity against the replication of Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2).…”
Section: Regular Articlementioning
confidence: 99%
“…To the best of our knowledge, the syntheses of long chain esters of acyclovir (laurate and palmitate) have been referenced only in the Gao et al 17) review in which yields of 37% are reported. Recently, Stankova et al 18,19) described the synthesis of acyclovir esters with peptidomimetics or with cinnamic acid using coupling reagents and evaluated in vitro for their antiviral activity against the replication of Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2).…”
Section: Regular Articlementioning
confidence: 99%